STRATEGI PENINGKATAN KUALITAS PELAYANAN PUBLIK DI RUMAH SAKIT TK. IV SINGARAJA KABUPATEN BULELENG PROVINSI BALI - Pertiwi, Ni Putu Nana Satrya; Wijaya, Komang Adi Sastra; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2022)
Rumah Sakit Tk. IV Singaraja is a hospital that joins the Datasemen Kesehatan Wilayah Singaraja (Denkesyah Singaraja) which carries out the main task of providing health support and health services. The problems contained in this study are Rumah Sakit Tk. IV Singaraja has not become the community priority as evidenced by the decrease in the number of patients in the period 2016-2020. This study aims to determine the strategy for improving the quality of public services in Rumah Sakit Tk. IV Singaraja. The method used in this research is a qualitative research method with a descriptive approach. The analysis in this study uses the service quality theory by Parasuraman, Zeitaml, and Berry (1988) and the strategic management theory by Thomas L. Wheelen and J. David Hunger (2015). The results of research findings on the dimensions of service quality are good, although there are still some aspects that are not optimal. In addition, in the strategic management process carried out by Rumah Sakit Tk. IV Singaraja is also good. However, there are still strategies that have not been maximized, namely the uneven distribution of programs to improve the quality of human resources for medical and non-medical personnel. To determine strategic recommendations, researchers also use SWOT analysis and SWOT matrix Keywords: Strategic Management, Public Service Quality, SWOT Analysis